answersLogoWhite

0


Best Answer

cos x - 2 sin x cos x = 0

-> cos x (1 - 2 sin x) = 0

=> cos x = 0 or 1 - 2 sin x = 0

cos x = 0:

x = π/2 + kπ

1 - 2 sin x = 0:

sin x = 1/2

-> x = π/6 + 2kπ or 5/6π + 2kπ

Thus

x = π/2 + kπ;

x = π/6 + 2kπ;

x = 5/6π + 2kπ

solve the original equation.

User Avatar

Wiki User

14y ago

Still curious? Ask our experts.

Chat with our AI personalities

SteveSteve
Knowledge is a journey, you know? We'll get there.
Chat with Steve
RafaRafa
There's no fun in playing it safe. Why not try something a little unhinged?
Chat with Rafa
LaoLao
The path is yours to walk; I am only here to hold up a mirror.
Chat with Lao

Add your answer:

Earn +20 pts
Q: What is cosx-2sinxcosx equals 0?
Write your answer...
Submit
Still have questions?
magnify glass
imp